PENGARUH KOMBINASI ABDOMINAL EXERCISE DAN PENGGUNAAN KORSET TERHADAP DIASTASIS RECTI ABDOMINIS IBU POST PARTUM PERVAGINAM - Ernawati, Ernawati; Oktaviani, Anisa Sevi (STIKes Medistra Indonesia, 2025)
Diastasis Recti Abdominis (DRA) is a common condition among postpartum women, characterized by the separation of the rectus abdominis muscles due to abdominal wall stretching during pregnancy. This condition may lead to physical discomfort, cosmetic concerns, and dysfunction of the abdominal and pelvic floor muscles. This study aims to examine the effect of abdominal muscle exercises combined with the use of an abdominal binder (corset) on reducing DRA in postpartum women. A pre-experimental design with a pretest-posttest approach was used. A total of 20 respondents were selected through simple random sampling. The intervention involved a combination of abdominal muscle exercises and corset usage. Digital calipers were used to measure the DRA before and after the intervention. The average DRA size decreased from 4.60 ± 0.6743 cm before the intervention to 4.15 ± 0.6245 cm after the intervention. Wilcoxon Signed Ranks Test showed a significant difference with p = 0.000 (p < 0.05). A total of 18 out of 20 respondents experienced a reduction in DRA size. The combination of abdominal muscle exercises and corset use is proven effective in reducing DRA, strengthening the abdominal muscles, and supporting postpartum recovery. This intervention is recommended as a simple, safe, and effective recovery strategy for postpartum women.